Use of dornase alfa in the management of life-threatening mucostasis in airway stents: its efficacy and safety - Demet Turan; Efsun Gonca Ugur Chousein; Mustafa Cortuk; Burcu Babaoğlu Elkhatroushi; Mehmet Akif Ozgul; Erdogan Cetinkaya (The Egyptian Journal of Bronchology)
Abstract Purpose Airway stents (AS) are a last-resort treatment for central airway obstructions when airway patency cannot be maintained above 50%, in patients unsuitable for surgery, or with recurrence after surgery. However, AS placement can cause complications, including life-threatening mucostasis, which is challenging to manage. Standard methods to prevent mucus retention often have limited efficacy. Dornase alfa, a mucolytic agent widely used in cystic fibrosis (CF) patients, has shown efficacy in secretion control in mechanically ventilated pediatric non-CF patients. This study evaluates the efficacy and safety of nebulized dornase alfa in managing AS-related life-threatening mucostasis. Results Fourteen patients (mean age 56.3 ± 15.6 years) with life-threatening mucostasis were identified among 255 stented patients (2017–2019). Eight had Y-shaped stents, and 6 had non-Y-shaped stents (5 hourglass and 1 OKI); 13 stents were placed for benign conditions and 1 for malignancy. Mucus grades (defined by Marchese et al.) and the number of bronchoscopies needed 6 months before and after dornase alfa were evaluated. Statistically significant decreases were observed in both mucus grades (2.36 ± 0.49 to 0.79 ± 0.59, p < 0.001) and the number of bronchoscopies per patient (3.21 ± 0.89 to 2.00 ± 1.04, p = 0.002). The shape of AS and the presence of bronchiectasis on thoracic computed tomography scans had no significant impact on mucostasis development. No side effects related to dornase alfa were observed. Conclusion Dornase alfa significantly reduced mucus burden and bronchoscopic interventions in AS-related life-threatening mucostasis, demonstrating its safety and efficacy for managing this complication.